The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/ijo.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

A novel interaction between the FLJ33534 locus and smoking in obesity: a genome-wide study of 14 131 Pakistani adults

Abstract: In summary, we have identified a novel interaction between smoking and variation at the FLJ33534 locus in relation to BMI in people from Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Although there was no evidence of association between variation at rs1051730 and BMI in never smokers, each additional risk allele (T) was associated with a BMI decrease of 0.16 and 0.33 kg/m 2 among former and current smokers respectively [165]. A separate study of 14131 Pakistani adults reported another gene × smoking interaction: the minor allele (T) in FLJ33534 was associated with lower BMI in current smokers and positively associated with BMI among adults who had never smoked [166]. A number of gene × smoking interactions were identified when African Americans and Caucasians were analysed separately, but no significant interactions were observed in the overall sample from the Southern Community Cohort Study [167].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 96%
“…Although there was no evidence of association between variation at rs1051730 and BMI in never smokers, each additional risk allele (T) was associated with a BMI decrease of 0.16 and 0.33 kg/m 2 among former and current smokers respectively [165]. A separate study of 14131 Pakistani adults reported another gene × smoking interaction: the minor allele (T) in FLJ33534 was associated with lower BMI in current smokers and positively associated with BMI among adults who had never smoked [166]. A number of gene × smoking interactions were identified when African Americans and Caucasians were analysed separately, but no significant interactions were observed in the overall sample from the Southern Community Cohort Study [167].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 96%
“…Among Asian Indians, Been et al confirmed the association of MC4R (rs12970134) with BMI (134). Genome-wide heterogeneity of variance analysis in 14,131 Pakistani individuals identified an interaction with smoking status and a novel obesity variant in FLJ33534 (rs140133294) on BMI (135). Meta-analysis of 9,881 African-Americans has demonstrated an association between FTO (rs3751812 and rs9941349) and obesity, while two smaller GWAS with individuals of African ancestry provide some evidence of replication of the association between MC4R (rs6567160 and rs17782313) and BMI (136,137).…”
Section: Gwas For Obesity In European and Non-european Populationsmentioning
confidence: 97%
“…When genetic variants in these genes were analysed with regards to environment, a stronger association between FTO , weight and living in an urban environment was found in comparison with those living in a rural environment . A novel interaction between smoking status and the FLJ33534 locus on BMI has recently been reported in a Pakistani population . G × G and G × E interaction remain largely unexplored due to statistical challenges associated with inadequate sample sizes but may explain some of the missing heritability .…”
Section: Polygenic Forms Of Obesity and Ethnic Diversitymentioning
confidence: 99%
“…Increased statistical power needed to identify SNPs associated with obesity traits under a recessive mode of inheritance is expected because of the high level of homozygosity in Pakistanis . GWAS for obesity traits have already been reported in South Asian populations . However, conducting a large‐scale genome‐wide association meta‐analysis in more than 100,000 participants of South Asian ancestry is critical to uncover the genetic basis of polygenic obesity in this population, as previously reported in European and East Asian studies .…”
Section: Genetic Elucidation Of Obesity In Pakistani Populationmentioning
confidence: 94%
“…FTO rs9939609 was more strongly associated with weight and BMI in siblings living in urban than rural area of India, an observation made in an independent study in South Asians . In the cross‐sectional PROMIS study, a genome‐wide heterogeneity of variance analysis for BMI was conducted in 14,131 participants . The intronic variant, rs140133294, in the FLJ33544 gene was associated with BMI variance.…”
Section: Genetic Elucidation Of Obesity In Pakistani Populationmentioning
confidence: 96%